Awareness about Tuberculosis in people living with HIV/AIDS: A cross Sectional Institutional Study. - Shrestha, Bikal; Pandya, Kapil; Patel, Barun; Shrestha, Rubina Shrestha; Kumar, Raj (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Worldwide, Tuberculosis (TB) is the most common opportunistic infection affecting HIV seropositive individuals and it remains the most common cause of death in patients with Acquired Immune Deficiency Syndrome. It is estimated that 50 to 60% of HIV infected people will develop TB in their lifetime. Keeping this in background this study was planned to assess the knowledge, attitudes and practices on TB in HIV positive patients. Methods: A cross sectional study was carried out in HIV positive individuals attending an ART centre. 100 attendees were selected by systematic random sampling method and interviewed with a pretested, structured questionnaire. Results: In the study 37.2% of respondents were not aware about air/droplet as a route of transmission of TB. Only 10% knew that infective organisms as a common opportunist infection in people with HIV & AIDS. 78.2% of the study population felt that the community will treat them differently if they suffer from TB and total of 57.7% confirmed an attitude of hiding the disease in them. Conclusion: The overall knowledge about TB in HIV positive individuals is low. Efforts must be made to counsel the patients about TB right in the first counselling session that the patient attends in ART centres so as to prevent spread of TB in the community. doi: http://dx.doi.org/10.3126/mjsbh.v13i1.12993